Timing in relay running - Boyadjian, A.; Bootsma, R. J. (Perceptual and Motor Skills, 1999)
Skillful performance in relay running requires that the athlete who is to take possession of the baton meets the baton carrier before reaching the end of the transmission zone while running at the highest speed possible. In the present study we examined the effects of variations in approach speed on the running behavior of the receiver. Kinematic analyses indicated that receivers regulated both the moment of initiation as well as the accelerative characteristics of their run. Contrary to the instructions given, baton carriers adapted their running speed as well to ensure a safe passage, making it difficult for the receiver to evaluate the appropriateness of their behavior.